Intrathecal Trastuzumab Treatment of the Neoplastic Meningitis due to Breast Cancer: A Case Report and Review of the Literature - Cristina Dumitrescu; Dominique Lossignol (Case Reports in Oncological Medicine)
We report the case of a 65-year-old woman, diagnosed with a breast cancer human epidermal growth factor receptor (HER2) previously negative, who developed leptomeningeal carcinomatosis and was treated with intrathecal (IT) trastuzumab (TST). After five doses of IT trastuzumab, at escalading doses, once weekly, the patient's neurological status stabilised, and that result was maintained for two months. There is evidence in the literature that breast cancer receptor status may change over time, and when it occurs, it may modify the therapeutical approach. We reviewed the pertinent literature and concluded that IT trastuzumab might be a promising treatment for patients with HER2-positive breast cancer leptomeningeal carcinomatosis.